2004
DOI: 10.1007/s11998-004-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nitroxide-mediated miniemulsion polymerization processes

Abstract: Living/controlled radical polymerizations provide significant advantages in the control of polymer resin microstructure compared to conventional radical polymerization. Advances in our ability to tailor polymer microstructure will enable improvements in coatings properties and possibly new applications of coating technologies. Adapting living radical polymerizations to heterogeneous media such as aqueous-based miniemulsion polymerization presents several challenges related to maintaining the livingness (the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…A potentially complicating factor is that DOWFAX 8390 was used as a surfactant by Pan et al [23,24] and Cunningham et al have reported that the R p of S miniemulsion polymerization using PS-T depends strongly on the DBS concentration (for similar particle size distributions) for reasons that are currently unclear. [25] The number of propagating radicals per particle (n) was calculated from Equation (2):…”
Section: Rate Of Polymerizationmentioning
confidence: 99%
“…A potentially complicating factor is that DOWFAX 8390 was used as a surfactant by Pan et al [23,24] and Cunningham et al have reported that the R p of S miniemulsion polymerization using PS-T depends strongly on the DBS concentration (for similar particle size distributions) for reasons that are currently unclear. [25] The number of propagating radicals per particle (n) was calculated from Equation (2):…”
Section: Rate Of Polymerizationmentioning
confidence: 99%
“…In most cases, S/TEMPO miniemulsion polymerizations using macroinitiator (polystyrene (PS)-TEMPO), [21,22] benzoyl peroxide/ TEMPO [23,24] or potassium persulfate/TEMPO [24][25][26][27] give R p values very similar to those in bulk. [28] Cunningham and coworkers [29,30] reported a strong dependence of R p in S/PS-TEMPO miniemulsion on the amount of the surfactant sodium dodecylbenzenesulfonate (SDBS) (the particle size distributions were ''nearly identical'' with a ''mean diameter'' of 150 nm), and speculated that SDBS or SDBS impurities consume nitroxide, thus resulting in an increase in R p . [29] Pan et al [31] reported that in the TEMPO-mediated thermal miniemulsion polymerization of S at 125 8C, the initial R p was approx.…”
Section: Introductionmentioning
confidence: 99%
“…However, PDI were slightly higher (~1.4-1.6) than those obtained under classical experimental conditions. Preformed molecular oil-soluble alkoxyamine, either based on TEMPO and derivatives [83,87,88] or SGI (MONAMS) [89][90][91][92], have been used for the polymerization of styrene and n-butyl acrylate in aqueous miniemulsion. A mathematical model developed by Ma et al predicted that under TEMPO-based molecular alkoxyamine initiation, the living fraction of the polymer should decrease with monomer conversion and the PDI should increase when reaching high monomer conversion [88].…”
Section: Oil-soluble Monocomponent Initiating Systemmentioning
confidence: 99%
“…A mathematical model developed by Ma et al predicted that under TEMPO-based molecular alkoxyamine initiation, the living fraction of the polymer should decrease with monomer conversion and the PDI should increase when reaching high monomer conversion [88]. However, for the polymerization of styrene initiated by the BST-TEMPO alkoxyamine (Figure 7.9a), adequate experimental conditions led to narrow molar mass distributions (PDI ~1.3) and high monomer conversions [83]. In contrast, with nBA in conjunction with ascorbic acid at 135°C [87], a higher PDI was obtained (-1.6 at 60% monomer conversion) compared to previous results involving the TIPNO-OH nitroxide.…”
Section: Oil-soluble Monocomponent Initiating Systemmentioning
confidence: 99%